Tissue Doppler Imaging in Acute and Critical Care: Enhancing Diagnostic Precision - Ugo Giulio Sisto; Daniele Orso; Davide Maione; Francesco Venturelli; Antonio De Luca (Medicina, 2025)
Background and Objectives: The introduction of portable ultrasound devices has transformed clinical practice in emergency medicine. Diagnostic accuracy and patient safety have been enhanced by point-of-care ultrasonography (POCUS), which has become a fundamental diagnostic and procedural tool. In addition to the standard clinical evaluation, POCUS provides quick patient assessments, allowing for the exclusion of life-threatening conditions and prognostication in different critical situations. Tissue Doppler imaging (TDI), as an advanced echocardiographic technique, offers additional quantitative data by measuring myocardial velocities, thereby improving the evaluation of systolic and diastolic ventricular function. The purpose of this review is to highlight the potential use of TDI in multiple acute and critical conditions. Materials and Methods: We conducted a narrative review of the main application topics for TDI. Results: TDI is an essential diagnostic and prognostic tool for acute coronary syndromes, assessing systolic or diastolic dysfunction, and etiological diagnosis of acute heart failure. It helps differentiate cardiogenic pulmonary edema from acute respiratory distress syndrome and identifies right ventricular systolic dysfunction in acute pulmonary embolism. TDI also facilitates distinctions between hypertension emergencies and urgencies and contributes to the stratification of atrial fibrillation reoccurrence risk. Furthermore, it aids in the differentiation of constrictive pericarditis from other restrictive cardiomyopathy patterns. In intensive care settings, TDI is particularly valuable during mechanical ventilation weaning, where elevated E/E’ values serve as a predictor of weaning failure. Due to its accessibility, rapid execution, and high reproducibility, it is suitable for longitudinal monitoring. Conclusions: TDI enhances the diagnostic precision, guides therapeutic strategies, and provides critical prognostic insights across a wide range of time-sensitive clinical scenarios, solidifying its role as an indispensable tool in modern emergency and critical care practice.